PENGEMBANGAN LATIHAN VO2MAX PADA CABANG OLAHRAGA SEPAK BOLA DI KELAS KHUSUS OLAHRAGA (KKO) SMA NEGERI 1 SLOGOHIMO WONOGIRI - Rino, Rino Nur Muhammad; Imam Hariadi (Universitas Muhammadiyah Cirebon, 2025)
Abstract This study aims to improve endurance in soccer through the development of a VO2Max training module product for special sports class players (KKO) SMA Negeri 1 Slogohimo Wonogiri. The development model uses procedural development. Product trials involved 3 experts with the subjects of 2 soccer experts and 1 learning media expert, small group test subjects 5 soccer players in special sports classes and large group test subjects 15 soccer players in special sports classes, the type of data used is quantitative (questionnaire) and qualitative (interview). The recapitulation of the validation results shows that the soccer practitioner expert gave a percentage of 87%, the media expert gave 87%, and the soccer coaching expert gave 88%. During the small group experiment involving 5 (five) players, the results reached 94%, while in the large group involving 15 (fifteen) players the results reached 95%. Through experiments and validation of each expert, the VO2Max training module that is being developed is considered very valid and feasible to be used as a reference for more interactive and interesting learning in the field of soccer and as a learning reference for soccer coaches.